Impact of Self-Help Group Formation on Social Indicators of Sustainability - SINGH, Surinder; Hansra, B.S (Journal of Extension Education, 2019)
Vegetable production has emerged as an important source of farm income from small farms in hilly states like Himachal Pradesh in India. Various researchers have studied agricultural sustainability taking into consideration three dimensions i.e. economic, environmental and social. Keeping in view the importance of the social sustainability which measures extent of social capability of farming system, present study was conducted in Himachal Pradesh to find out the ways to strengthen farm sustainability. Farm sustainability of self-help group member farmers and non-member farmers was studied and compared. Study revealed that the social sustainability of vegetable growers who were members of self-help groups was significantly higher when compared to non-member farmers.